THE ROLE OF LEADERSHIP HEAD OF SCHOOL INDICATORS IN THE QUALITY OF LEARNING IN STATE SCHOOL 34 BANYUASIN III - Yunita Iryani; Happy Fitria; Mulyadi Mulyadi (Esteem Journal of English Education Study Programme, 2023)
Schools as an educational institution face two demands, namely the demands of the community and the demands of the business world, the researcher wants to find out more about how the implementation of Principal Leadership Management in Quality of Learning at the 34 Banyuasin III State Elementary School. The research used descriptive qualitative research method. Qualitative method used to analyze data in the form of information, such as observations, documentation, using two ways of thinking and for the informant were administrative staff at the 34 Banyuasin III State Elementary School. From the results of this study, it was found that the principal always distributes educators in accordance with the fields they are skilled in and assigns tasks to education personnel in accordance with their disciplines. In relation to the world of education, learning facilities can be positioned as part of supporting student success which is called student learning achievement.